The Use of β-Blockers in Heart Failure with Reduced Ejection Fraction - Masarone, Daniele; Martucci, Maria Luigia; Errigo, Vittoria; Pacileo, Giuseppe (Journal of cardiovascular development and disease, 2021)
Treatment with β-blockers is the main strategy for managing patients with heart failure and reduced ejection fraction because of their ability to reverse the neurohumoral effects of the sympathetic nervous system, with consequent prognostic and symptomatic benefits. However, to date, they are underused, mainly because of the misconception that hypotension and bradycardia may worsen the haemodynamic status of patients with HFrEF and because of the presence of comorbidities falsely believed to be absolute contraindications to their use. To promote proper use of β-blockers in this article, we review the clinical pharmacology of β-blockers, the evidence of the beneficial effects of these drugs in heart failure with reduced ejection fraction, and the current guidelines for their use in clinical practice and in the presence of comorbidities (e.g., pulmonary disease, diabetes, atrial fibrillation, peripheral arterial disease, etc.). It is hoped that the practical approach discussed in this review will allow for a proper diffusion of knowledge about the correct use of β-blockers and the drug-disease interactions to achieve their increased use and titration, as well as for the selection of a specific agent with a view to a properly tailored approach for HFrEF patients.